Research progress on the mechanism of neural electrical information transmission in acupuncture intervention of depression - Shu-juan LI; Min XIAO; Chong-bing MA; Xing-ke YAN (World Journal of Acupuncture - Moxibustion)
Acupuncture has been proven effective in treating depressive disorders, and its neuroelectrophysiological mechanisms have drawn increasing scientific attention. This paper reviews recent neuroelectrophysiological studies on acupuncture in the treatment of depressive disorders. Studies have shown that acupuncture can modulate the Alpha and Theta wave frequencies and amplitudes of electroencephalograms; improve the latency and amplitude of event-related potential such as P300 and mismatch negativity (MMN); enhance the amplitude of motor-evoked potential and short-interval intracortical inhibition as measured by transcranial magnetic stimulation-electromyography (TMS-EMG); regulate both spontaneous and induced rhythmic activities; increase motor cortex excitability; and promote the electrical signal transmission in neuronal clusters. Acupuncture can enhance the long-term potentiation (LTP) detected by PCRT, repair the plasticity of synaptic functions, and promote the transmission of synaptic information; lower the action potential (AP) and population spike (PS) membrane voltage detected by PCRT, inhibit abnormal neuronal excitability, and restore electrical signal transmission across neuronal membranes. These findings, as summarized in this review, may reflect potential neuroelectrical signal transmission mechanisms involved in the acupuncture interventions for depressive disorders.